2017
DOI: 10.29384/rbfm.2017.v11.n2.p16-20
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de feixes de TC utilizando Espectrometria Compton

Abstract: ResumoÉ essencial obter espectros dos raios X em tomografia computadorizada (TC), visando obter parâmetros que caracterizam a qualidade do feixe e o desempenho do equipamento. Entretanto, os fluxos de fótons em TC são demasiado elevados para se medir os espectros diretamente com detetores comuns. Neste trabalho, foi projetado um espectrômetro Compton, com um detetor de telureto de cádmico (CdTe), para obter o espectro de feixes de TC, a partir da medição do espectro do feixe espalhado a 90 o por uma haste de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Figure 31.a shows the X-ray spectra and Table 3 presents their physical characteristics. These spectra are in good agreement with those obtained by indirect measurement performed by Terini (Terini et al, 2017), as shown in Figure 31.b. The radiation emission distribution from the modelled line focal spot follows a Gaussian distribution with FWHM equal to 0.9 mm, which is the optical length of the actual focal spot length (see, Figure 13).…”
Section:  Focal Spotsupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 31.a shows the X-ray spectra and Table 3 presents their physical characteristics. These spectra are in good agreement with those obtained by indirect measurement performed by Terini (Terini et al, 2017), as shown in Figure 31.b. The radiation emission distribution from the modelled line focal spot follows a Gaussian distribution with FWHM equal to 0.9 mm, which is the optical length of the actual focal spot length (see, Figure 13).…”
Section:  Focal Spotsupporting
confidence: 90%
“…Percentage difference with respect to the experimental data up to 23.4% ( =10mm) and 52.9% ( =20mm) for 80kV X-ray spectrum and head bowtie filter, and up to 8.9% ( =10mm) and 11.6% ( =40mm) for 140kV and 120kV X-ray spectra, respectively, for body bowtie filter were found. With respect to the X-ray spectra, they were generated by the semi-empirical TBC model (Costa et al, 2007, Lopez Gonzales et al, 2015 following the spectra characteristics measured by indirect methods (Terini et al, 2017). The division of the whole MC simulation process of the CT helical scan modes into two stages showed benefits in terms of simulation time and disk storage administrations, also, allowed good performance in error identifications in the MC modelling process.…”
Section: Dose Line Integral Versus Dose Length Productmentioning
confidence: 99%